The Use of Number Head Together to Improve Vocabulary Mastery of the Eight Grade Students of Smpn 16 Malang in Academic Year 2019/2020 - Anggia Nararia Septona; Indrawati Pusparini (ANFA MEDIATAMA, 2022)
The method used in this research was classroom action research. The researcher conducted this research from February until March 2020 in SMPN 16 Malang. The subject was the students of VIIIH in 2019/2020 academic year. This class consists of 30 students, 17 boys and 13 girls. In collecting the data, the researcher use observation and test. The test were given in pre-test, test 1 and test 2. The researcher analyzed the mean score of each test to find out the improvement of students vocabulary mastery after the action was conducted. The researcher conducted the action the students‟ vocabulary mastery increased optimally. It could be seen from the score that pre-test is 72,3, post-test 1 is 78,2, and post-test 2 is 79,8. Percentage the criteria of success on the pre-test is 53,3% and on the post-test 2 is 73,3%, from pre- test to post-test 2 is 20% After applying the action the researcher was able to solve the problem in improving vocabulary mastery. The students were able to take the word meaning based on the context. By using number head together technique in teaching vocabulary, students could easly understand and memorize vocabulary, the students are enthusiastic and enjoy during teaching learning process.